Development and Preliminary Validation of NIHSS-SDKI and CNS-SDKI Tools for Nursing Diagnosis in Stroke Care - Fitriana, Erlis Eka; Haryanto, Haryanto; Supriadi, Supriadi; Hastuti, Lidia; Surtikanti, Surtikanti (Universitas Pendidikan Indonesia, 2025)
Introduction: Accurate assessment of stroke severity is a critical component of nursing care. The NIHSS and CNS are standardized neurological instruments commonly used to evaluate stroke severity. Integrating NIHSS and CNS with the Indonesian nursing diagnosis standard (SDKI) offers practical benefits for nurses, as SDKI is tailored to the conditions of patients in Indonesia. Objective : The objective of this study is to evaluate the effectiveness of combining NIHSS and CNS severity assessments with SDKI in improving the accuracy of nursing diagnoses and determining stroke severity in patients. Methods: The research design used was Randomized Controlled Trial (RCT), single blind. The sample consisted of 55 stroke patients admitted to the neurological care unit using probability sampling technique with a simple random sampling approach, where sampling was carried out in accordance with predetermined inclusion criteria: non hemorrhagic stroke patients, respondents' age 18 years, and willing to become research subjects. Assessment of severity was carried out using the NIHSS and CNS instruments, which were combined with the SDKI to determine nursing diagnoses. Assessment was carried out for 5 days of patient care. Results: Mann-Whitney test analysis in the NIHSS group and CNS group showed a p-value (0.05), meaning that there was no difference between the application of NIHSS and CNS assessment on determining the degree of severity and the number of nursing diagnoses in stroke patients. Conclusions: This study shows that both NIHSS-SDKI and CNS-SDKI are effective in detecting changes in the clinical condition of stroke patients from day one to day five.